The structure of a modern school – case study - Vilbikienė, Grėtė (Journal of Architecture and Urbanism, 2022)
The aim of this article is to test and apply the developed methodology of research on the correlation between the physical learning environment and education, analysing Vilnius Geroji Viltis Progymnasium. The article analyses functional-spatial structure and usability of the selected school (applying the principles of post occupancy evaluation (POE), and analyses the school culture and the needs of school community groups, which are compared with modern Lithuanian educational goals and objectives. The functional-spatial structure of the analysed school is compared with the general school model of the 21st century formed in the author’s previous research, which distinguishes 7 features of the physical learning environment that define the quality of the modern learning environment. It also examines the extent to which the current physical school environment satisfies and meets the school culture and community needs. The article provides guidelines for the implementation of the harmony of school culture (values and needs) and its physical environment, which allows each school to self-assess the physical learning environment and its cultural and 21st century school physical environment characteristics and assumptions and opportunities to meet them.